2009
DOI: 10.1097/lbr.0b013e31819f273f
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Bronchoscopic Intervention With Resector Balloon

Abstract: In this study a novel therapeutic bronchoscopic technique, balloon bronchoplasty with resector balloon, was used in 128 procedures for 112 consecutive patients with airway obstruction from lung cancer or granulation tissue. All procedures, except 4, were performed with a rigid bronchoscope under general anesthesia. The remainder were performed with a flexible bronchoscope under local anesthesia. In all procedures, balloon bronchoplasty was the primary method and we achieved 100% success with no major immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The treatment is performed in a single session, and in total 100 to 300 segmental bronchi could be treated during a 60-minute bronchoscopy. 25 The use was then extended to patients with severe COPD, where bronchiolitis contributed mainly to the airflow limitation. Studies have shown that bioptically the number of goblet cells was reduced, so that regeneration of the bronchial mucosa is assumed to be the mechanism of action.…”
Section: Chronic Bronchitismentioning
confidence: 99%
“…The treatment is performed in a single session, and in total 100 to 300 segmental bronchi could be treated during a 60-minute bronchoscopy. 25 The use was then extended to patients with severe COPD, where bronchiolitis contributed mainly to the airflow limitation. Studies have shown that bioptically the number of goblet cells was reduced, so that regeneration of the bronchial mucosa is assumed to be the mechanism of action.…”
Section: Chronic Bronchitismentioning
confidence: 99%
“…Description of treatment The Karakoca resector balloon developed for the treatment of airway obstruction [41] has been found a place in the management of chronic bronchitis patients. The device consists of a latex balloon covered with a mesh structure of 0.2-mm polyurethane/lycra fibres, mounted onto the distal end of long single-lumen polyethylene tube.…”
Section: Karakoca Balloon Desobstruction Proceduresmentioning
confidence: 99%